A comprehensive survey on spectrum sharing: Architecture, energy efficiency and security issues. (1st February 2018) - Kour, Haneet; Jha, Rakesh Kumar; Jain, Sanjeev
Abstract: The future generation networks (5G) are expected to achieve high data rates, reduced latency, increased spectral efficiency and energy efficiency of the system. Since the available spectrum is a scarce resource, its efficient utilization is the prime focus of the next generation networks. Spectrum Sharing is a key aspect that is gaining significant attention as it can prove to be beneficial in meeting the above requirements. In this paper we present an exhaustive survey of spectrum sharing for future generation networks. We discuss the different techniques and methods of spectrum sharing based on which a general architecture has been presented. Next, we discuss spectrum sensing, network selection and channel allocation, power optimization in spectrum sharing as well as the security issues associated. Based on the survey a four layer architecture has been proposed depicting the complete spectrum sharing scenario from spectrum sensing till the security issues. Modern technologies such as Massive MIMO, SWIPT, spectrum harvesting, spectrum relaying have been incorporated in the architecture for optimizing the power during spectrum sharing. A detailed analysis of security attacks has also been presented in the paper. Two application scenarios have been discussed where in spectrum sharing can offer huge advantages to meet the high bandwidth requirements. The paper also includes a list of the current projects that are being conducted by various research groups and institutions on spectrum sharing, for the next generation networks. Graphical abstract: Proposed four layer architecture depicting complete spectrum sharing scenario. Starting from the first aspect which is spectrum sensing followed by Network Selection and Channel Allocation, Spectrum Sharing along with power optimization, up till the security attacks during spectrum sharing. Highlights: Review of existing research on spectrum sharing along with the various energy efficient techniques for power optimization. A general architecture for spectrum sharing incorporating the diverse schemes. Proposed four layer architecture depicting complete spectrum sharing scenario. Detailed analysis of security issues during spectrum sharing. Lessons learned and future work.